Site V Surgery for Temporal Migraine Headaches. Issue 6 (June 2020) - Baldelli, Ilaria; Mangialardi, Maria Lucia; Raposio, Edoardo
Abstract : Background: Auriculotemporal nerve is demonstrated to contribute to migraine pain in temporal area. In particular, its relationship with the superficial temporal artery in the soft tissues superficial to the temporal parietal fascia has attracted researchers' attention for many decades. The objective of this review was to explore whether site V nerve surgical decompression is effective for pain relief in temporal area. Methods: A literature search, according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, was conducted to evaluate the surgical treatment of auriculotemporal migraine. Inclusion was based on studies written in English, published between 2000 and February 2020, containing a diagnosis of migraine in compliance with the classification of the International Headache Society. The treatment must consist of surgical procedures involving the auriculotemporal nerve and/or arteries in site V, with outcome data available for at least 3 months. Results: Three hundred twenty-four records were identified after duplicates were removed, 31 full-text articles were assessed for eligibility, and 2 records were selected for inclusion. A total of 77 patients were included in the review. A direct approach at the anatomical site identified with careful physical examination and confirmed with a handheld Doppler probe is generally performed under local anesthesia. Blunt dissection to the superficial temporal fascia to expose the auriculotemporal nerve and the superficial temporal artery is followed by artery cauterization/ligament and eventual nerve transection/avulsion. Site V surgery results in a success rate from 79% to 97%. Conclusions: Despite the recent advances in extracranial trigger site surgery and a success rate (>50% improvement) from 79% to 97%, site V decompression is still poorly described. Elaborate randomized trials are needed with accurate reporting of patient selection, surgical procedure, adverse events, recurrencies or appearance of new trigger points, quality of life outcome, and longer follow-up times.